(untitled) (Academic Journal of Internal Affairs, 2021)
The use of distinctive signs can cause extreme stress to the driver and also to his immediate traffic environment while driving. It is therefore important to prepare drivers who use distinctive signs. My research at the Institute of Traffic Psychology of the Police presents the extension of simulator tests during the active application of distinctive markings under laboratory conditions. As a result of the study, I found that the effect of distinctive signals can be detected in the reaction time.